Synthesis and Antiinflammatory Activity of 3-(3-Chloro-4-fluorophenyl)-2-Substituted Phenyl-4-Thiazolidinones - Srinivasa Murthy, M.; Krishna Rao, Gopala; Sanjay Pai, P.N.; Nargund, L.V.G. (Asian Journal of Chemistry, 2016)
3-Chloro-4-fluoroaniline on condensation with various aromatic aldehydes afforded corresponding Schiff bases 1. Further, these Schiff bases were converted into 3-(3-chloro-4-fluorophenyl)-2-substituted phenyl-4-thiazolidnones (2) by the action of thioglycollic acid. The structures of the synthesized compounds were characterized by their spectral studies. The antiinflammatory activity data of 2 was also presented.